Welcome to Mitchell's Plain Filming a 'Model Township' during Apartheid - Ommundsen Pessoa, Ludmila (Africae Monographs, 2023)
Under the apartheid regime, South Africa's Mitchell's Plain, situated close to Cape Town, was devised as a "model township." A cutting-edge urban planning scheme would provide middle-class Coloured people-evacuated from their homes by racialised rehousing programmes-with exemplary living conditions. This flagship for the regime was inaugurated with fanfare in 1976, and heavily publicised not just within South Africa but also in the international press. Cohorts of political leaders and journalists were invited to admire first-hand how racial segregation could be paired with progressive social planning. A documentary film was commissioned for worldwide distribution: Mitchells Plain (1980). Like other well-laid plans, however, Mitchell's Plain would foil the designs of its architects. The vaunted utopian township was, for its inhabitants, deeply flawed: essential facilities such as schools and transport were thoroughly inadequate to the population's needs. These sources of frustration generated a groundswell of civic activism. While the government had banked on separating the Coloured population from the national liberation movement, in 1983, Mitchell's plain acquired important symbolic status as the birthplace of the United Democratic Front, an umbrella organisation of anti-apartheid associations. This event marked a turning point in the history of South Africa's struggle for freedom. This study chronicles the fortunes of Mitchell's Plain: its conception and role as propaganda for the apartheid regime. It draws on official documentary sources, but also on interviews with the various social actors whose life-experience conveys a very different image of the process, to reconstitute from a critical and historical perspective, the ill-fated window-dressing efforts of the National Party government during its declining years.